The last scream: the distress call of a probably extinct Brazilian anuran (Holoaden bradei Lutz, 1958) - Martinelli, Amanda; Toledo, Luís Felipe (Zootaxa, 2016)
The genus Holoaden Miranda-Ribeiro (Anura, Craugastoridae, Holoadeninae) includes four species endemic to the southeastern Brazilian Atlantic Forest, which occur in cloud forests at high elevations (Lutz 1958, Pombal et al. 2008, Martins & Zaher 2013). Out of these, two species are considered threatened by Ministério do Meio Ambiente (2014): H. bradei is classified as critically endangered (CR) and H. luederwaldti as endangered (EN). Holoaden bradei might be already extinct in the wild, as it has not been recorded in the last 40 years in spite of intense scientific activity within its original distribution range (Rocha & van Sluys 2004). The advertisement call has been described only for Holoaden luederwaldti (Martins 2010). Call descriptions, especially of advertisement calls, are important sources of evidence in taxonomic and phylogenetic studies (Roy 1996, Toledo et al. 2007, Andrade et al. 2016). However, there are other call types (see classification in Toledo et al. 2015) that can be used in absence of advertisement calls (e.g., Grenat & Martino 2013). We recently had access to a recording made in 1960’s of the distress call of H. bradei. We hereby describe this call.